Republic of Madagascar : Second and Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria-Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Republic of Madagascar. (IMF Staff Country Reports; Country Report ;, 2008)
There has been progress in strengthening public financial management; however, improving budget execution and strengthening public finances is required. The tax and custom administration reforms will help bolster private sector-led growth and meet the ambitious revenue target to finance priority expenditure. Monetary and exchange rate policy is required to reduce inflation while preventing an overshooting of the exchange rate. Further progress is needed to foster financial sector development. A more ambitious rehabilitation plan for the electricity sector needs to be designed and implemented with urgency.